Bacterial Communities Associated With Four Blooming Scyphozoan Jellyfish: Potential Species-Specific Consequences for Marine Organisms and Humans Health - Peng, Saijun; Hao, Wenjin; Li, Yongxue; Wang, Lei; Sun, Tingting; Zhao, Jianmin; Dong, Zhijun (Frontiers in Microbiology, 2021)
Cnidarians have large surface areas available for colonization by microbial organisms, which serve a multitude of functions in the environment. However, relatively few studies have been conducted on scyphozoan-associated microbial communities. Blooms of scyphozoan species are common worldwide and can have numerous deleterious consequences on the marine ecosystem. Four scyphozoan species, Aurelia coerulea, Cyanea nozakii, Nemopilema nomurai, and Rhopilema esculentum, form large blooms in Chinese seas. In this study, we analyzed the bacterial communities associated with these four jellyfish based on 16S rRNA gene sequencing. We found that the bacterial communities associated with each scyphozoan species were significantly different from each other and from those of the surrounding seawater. There were no significant differences between the bacterial communities associated with different body parts of the four scyphozoan jellyfish. Core bacteria in various compartments of the four scyphozoan taxa comprised 57 OTUs (Operational Taxonomic Units), dominated by genera Mycoplasma, Vibrio, Ralstonia, Tenacibaculum, Shingomonas and Phyllobacterium. FAPROTAX function prediction revealed that jellyfish could influence microbially mediated biogeochemical cycles, compound degradation and transmit pathogens in regions where they proliferate. Finally, Six genera of potentially pathogenic bacteria associated with the scyphozoans were detected: Vibrio, Mycoplasma, Ralstonia, Tenacibaculum, Nautella, and Acinetobacter. Our study suggests that blooms of these four common scyphozoans may cause jellyfish species-specific impacts on element cycling in marine ecosystems, and serve as vectors of pathogenic bacteria to threaten other marine organisms and human health.